A Review of Machine Learning Techniques over Big Data Case Studies (International Journal of Innovative Research in Computer Science & Technology, 2020)
In the recent years, Data has increased  exponentially and is termed as Big Data. Data Amount,  Data Speed and Data Variation are three major parameters  of Big Data. There are many challenges which have tuned  up out of which Data Storage, Data Analysis and Data  Management are the biggest ones. In order to deal with  these challenges, Machine Learning, a subset of Artificial  Intelligence provides various tools and techniques. This  paper gives a detail about Big Data and Machine Learning.  It also includes detailed literature review on various Big  Data case studies which are solved by Machine Learning  Techniques.
Keywords: Big Data; Data Analytics; Machine Learning; Deep Neural Network; Supervised Learning; Neural Net; Data Mining; Computing